2020
DOI: 10.1097/md.0000000000018948
|View full text |Cite
|
Sign up to set email alerts
|

Direct acting antivirals treatment for hepatitis C virus infection does not increase the incidence of de novo hepatocellular carcinoma occurrence

Abstract: Hepatitis C virus (HCV) infection is a major cause of chronic liver disease, with approximately 71 million chronically infected individuals worldwide. Clinical care for patients with HCV-related liver disease has advanced considerably thanks to an enhanced understanding of the pathophysiology of the disease, and because of developments in diagnostic procedures and improvements in therapy and prevention. These European Association for the Study of the Liver Recommendations on Treatment of Hepatitis C describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 166 publications
(174 reference statements)
1
8
0
Order By: Relevance
“…Eight studies (n = 66,636) reported the adjusted HRs for mortality among DAA-treated patients who attained SVR vs nonresponders. 33,36,[57][58][59][60][61][62] Three studies (n = 3178) reported the adjusted HRs/IRRs for decompensation (including one study where all patients had HCC), 59,61,62 12 studies (n = 59,691) for HCC occurre nce 43,44,48,61,[63][64][65][66][67][68][69][70] and three (n = 527) for HCC recurrence 59,68,71 (Table 2). The median duration of follow-up after SVR ranged from 14 to 26, 20 to 21, 10 to 37 and 5 to 23 months for mortality, decompensation, HCC occurrence and HCC recurrence, respectively (Table S3).…”
Section: Efficacy Of Svr On Mortality and Disease Progression Amongmentioning
confidence: 99%
“…Eight studies (n = 66,636) reported the adjusted HRs for mortality among DAA-treated patients who attained SVR vs nonresponders. 33,36,[57][58][59][60][61][62] Three studies (n = 3178) reported the adjusted HRs/IRRs for decompensation (including one study where all patients had HCC), 59,61,62 12 studies (n = 59,691) for HCC occurre nce 43,44,48,61,[63][64][65][66][67][68][69][70] and three (n = 527) for HCC recurrence 59,68,71 (Table 2). The median duration of follow-up after SVR ranged from 14 to 26, 20 to 21, 10 to 37 and 5 to 23 months for mortality, decompensation, HCC occurrence and HCC recurrence, respectively (Table S3).…”
Section: Efficacy Of Svr On Mortality and Disease Progression Amongmentioning
confidence: 99%
“…After one year of follow up HCC developed more in not treated group with a significant difference between treated and not treated groups , as 11% of not treated group developed HCC compared to 5.5% only of treated group, similar results were detected by Ioannou et al, [8] who documented that HCC incidence was lower in the treated group who achieved SVR (0.43 per 100 patient-years) than in control group (1.15 per 100 patient-years), also, Kanwal et al, [9] documented that HCC developed in 183 patients with treatment during follow up at an annual incidence of 0.90 (or 0.90%, 95% CI, 0.77-1.03%), this rate was considerably lower than the 3.45 incidence rate in patients without treatment (3.45%, 95% CI, 2.73-4.18), in addition to Nahon et al, [10] who documented that there is a significant difference between treatment and control groups as regards HCC occurrence as number of patients with HCC at treatment group was 15 patients (4.5%) while number of patients with HCC at not treated group was 154 patients (35.1%) (P<.001), also, Buonomo et al, [11] documented that direct acting antivirals treatment for hepatitis C virus infection does not increase the incidence of de novo hepatocellular carcinoma occurrence.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, non treated group with HCC (group IV) total bilirubin is higher than treated group with HCC (group III) with statistical significant difference, this can be explained by improvement in progression of cirrhosis after DAAs treatment, also, Pereira et al, [13] documented that DAA-induced SVR remains durable and is associated with an excellent clinical prognosis in patients with compensated advanced liver disease and with improvement or disease stabilization in decompensated patients. SVR is associated with a low risk of HCC occurrence or disease progression, especially in the presence of other causes of liver injury, in addition to Buonomo et al, [11] DAAs have a great efficacy in the eradication of HCV infection, these treatments were also effective in reducing the incidence of several complications of cirrhosis, such as ascites, jaundice and encephalopathy.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the analysis of the ITA.LI.CA (Italian Liver Cancer) register documented a 4% drop per quinquennium of HCV-related hepatocellular carcinoma (HCC) from 2000 to 2014 [ 11 ]. The recent introduction of direct-acting antivirals favorably contributed to HCV infection eradication, with valuable evidence of a lower rate of HCC development in patients who achieved sustained virologic response at 12 weeks post-treatment [ 24 ]. In this frame, access to hepatitis C treatment was expressly recommended by the WHO Thirteenth General Programme of Work (GPW13) as an indicator of country-based universal health coverage [ 25 ].…”
Section: Discussionmentioning
confidence: 99%